Improvement of Mechanical Properties in Polypropylene- and Glass-Fibre-Reinforced Peach Shell Lightweight Concrete - Fan Wu; Changwu Liu; Zhaofeng Diao; Bo Feng; Wei Sun; Xiaolong Li; Shuang Zhao (Advances in Materials Science and Engineering)
The use of the polypropylene fibre and glass fibre with different volume fractions to improve the mechanical properties of peach shell lightweight concrete was investigated in this study. The volume fractions of 0.25%, 0.50%, and 0.75% were used for each fibre. The results showed that, as the polypropylene fibre and glass fibre were added into peach shell concrete, the density was reduced by up to 6.1% and the compressive strength, splitting tensile strength, and flexural strength were increased by 19.1%, 54.3%, and 38.6%, respectively. The highest compressive strength, splitting tensile strength, and flexural strength of 29.3 MPa, 2.87 MPa, and 3.09 MPa, respectively, were produced by peach shell concrete with 0.75% glass fibre. The results indicated that the incorporation of fibres significantly enhanced the postfailure toughness of peach shell concrete. It was found that the glass fibre was more effective than the polypropylene fibre in improving the mechanical properties of peach shell concrete. Although the incorporation of fibres slightly increased the water absorption and porosity, the type and content of fibres had no significant effect on water absorption and porosity. Therefore, the mechanical properties of peach shell lightweight concrete can be improved by adding polypropylene fibres and glass fibres.